ASPECTOS MERCADOLÓGICOS DA PRODUÇÃO DE COMPENSADOS DO ESTADO DO PARANÁ - Ribaski, Nayara Guetten (2012)
For any business to succeed in the current struggling competitive market, it is necessary to have an understanding about the development and behavior of the segment in which it actuates in order to make the best decisions. The present work aims at describing the profile of the plywood industry of Parana from the perspective of its producers. The followings are the specific goals: classify the plywood board produced in Parana, analyze the perception of plywood manufacturers about the current market situation and evaluate the events that affect its production, such as the substitute plywood board and the competitiveness. A combined exploratory and descriptive questionnaire with open and closed questions was used as an instrument of the present research. The collection of data was made in two stages. The first one, between July and September 2010, with 89 questionnaires sent to plywood industries from the State of Paraná. The second one was made between July and September 2012, with 81 questionnaires sent to the same industries, although many of those had been closed and/or jointed by major companies. The SWOT (strengths, weaknesses, opportunities and threats) methodology was applied in the open questions whereas the quantitative treatment was inserted in the closed ones. In the first stage, of 30.34% industries participated in the survey and 27.16% in the second stage, both having obtained a sampling error below 13.5%. By the analysis of the market structure, it was noticed that during the 80`s the plywood manufacturers strategically chose to supply the external market seeking for higher profits due to the appreciation of the American dollar. The United States became the main client to the detriment of the internal market. The Brazilian market niche has been taken over by the reconstituted wood fiber board, turning this ones into substitute goods for the plywood in different segments of actuation, by this means, changing the elasticity price of the demand. In 2010, it was observed that the production of the operating companies in the market declined 56% in comparison with 2008. In 2012, 60% of the production is driven towards the internal market in order to take advantage of the civil construction boom. The remainder of the export production took new destinations in 2010, focusing on the emerging markets such as the South America, Middle East and Africa for demanding less technical and/or commercial specific barriers to the plywood as it requested by the United Stated and Europe. The most mentioned barriers were: proof of legal origin of the wood and demand with the quality control. Regarding the events that affect the production of plywood boards, it was pointed that 93% of the selling price is the greatest problem and the cost for their production is indeed high. With reference to the export, the commercial value is a daunting factor to the producers. 52% of participants believe there is a substitute good for the plywood of which 57% out of this group consider to be the MDF The plywood board segment was giving signs of decrease in its production since 2004 due to events such as high price in its production, low competitiveness and high cost of the land achieving its summit with the American real estate crisis. Despite the fragility in this segment, the participants of the survey did not demonstrate to be aware about these situations. Amongst the conclusions, it was mentioned that the manufacturers are not fully aware about the market in which they operate, turning difficult for them to make the best decisions. Or else, such awareness has not been mentioned on purpose in order not to characterize the critical current situation, which could create a barrier for potential loan or credit market. The plywood market comes in a stage of maturity and decline, that because the company did nothing to prevent the situation, however there are strategies to prevent the decline.